2024
DOI: 10.1037/trm0000441
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and spirituality among adults with chronic illness.

Abstract: The present study examined relationships between religious and spiritual factors (i.e., attitudes toward God, religious commitment, and spiritual bypass) and posttraumatic growth, in a sample of individuals living with chronic illness (N = 139). Findings from hierarchical regression analyses suggest that anger with God, comfort with God, and psychological avoidance each contribute to the experience of PTG within the sample. Based on these results, mental health professionals have a crucial role in assessing cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The belief in a higher power and finding meaning in suffering were common themes. Zeligman and Fakhro (2023) found that spirituality contributed to posttraumatic growth among adults with chronic illness, supporting our findings that faith can lead to positive psychological adjustments (Zeligman & Fakhro, 2023). Additionally, Reynolds et al (2016) in their meta-analytic review, confirmed that spiritual coping is associated with better psychosocial adjustment and physical health, particularly in youth with chronic illness (Reynolds et al, 2016).…”
Section: E-issn: 3041-8542supporting
confidence: 74%
See 2 more Smart Citations
“…The belief in a higher power and finding meaning in suffering were common themes. Zeligman and Fakhro (2023) found that spirituality contributed to posttraumatic growth among adults with chronic illness, supporting our findings that faith can lead to positive psychological adjustments (Zeligman & Fakhro, 2023). Additionally, Reynolds et al (2016) in their meta-analytic review, confirmed that spiritual coping is associated with better psychosocial adjustment and physical health, particularly in youth with chronic illness (Reynolds et al, 2016).…”
Section: E-issn: 3041-8542supporting
confidence: 74%
“…hronic illnesses, such as heart failure, cancer, diabetes, and chronic pain conditions, impose substantial physical and emotional challenges (Coutinho, 2021;Pan & Sánchez, 2022;Suksatan et al, 2022;Thomas et al, 2022;Weitkamp & Bodenmann, 2022;Zeligman & Fakhro, 2023). Research has shown that individuals often turn to spiritual and religious practices to navigate these difficulties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rose et al (2014) found that the height level of religious commitment among Black adolescents indicated by attending regular religious services and activities was linked to heightened levels of positive psychosocial well-being and decreased levels of psychosocial dysfunction. In addition, Zeligman and Fakhro (2023) examined the connection between posttraumatic growth and spirituality in adults with chronic illnesses and found that religious commitment is crucial in mitigating symptoms of psychological distress.…”
Section: Introductionmentioning
confidence: 99%